2007
DOI: 10.1051/0004-6361:20077200
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar kicks andγ-ray burst

Abstract: Aims. We use the supernova-GRB (γ-ray burst) association and assume that the GRB asymmetric explosions produce pulsars in order to test the consistency of distributions of modeled and observed pulsar-kick velocities. Methods. The deduced distribution of kick velocity from the model of GRB and the observed kick distribution of radio pulsars are checked by a K-S test. Results. These two distributions are found to come from the same parent population. Conclusions. This result may indicate that GRBs could really b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Pulsars are created in supernovae, and the birth process is expected to impart a high 'kick velocity'. Various mechanisms have been proposed for these kicks, including an asymmetric neutrino emission in the presence of super-strong magnetic fields (Lai & Qian 1998), a postnatal electromagnetic rocket mechanism (Harrison & Tademaru 1975), asymmetric explosion of γ-ray bursts (Cui et al 2007) and hydrodynamical instabilities in the collapsed supernova core (Lai & Goldreich 2000). While the evidence for such kicks is unequivocal (Johnston et al 2005), their physical origin remains unclear.…”
Section: Proper Motionsmentioning
confidence: 99%
“…Pulsars are created in supernovae, and the birth process is expected to impart a high 'kick velocity'. Various mechanisms have been proposed for these kicks, including an asymmetric neutrino emission in the presence of super-strong magnetic fields (Lai & Qian 1998), a postnatal electromagnetic rocket mechanism (Harrison & Tademaru 1975), asymmetric explosion of γ-ray bursts (Cui et al 2007) and hydrodynamical instabilities in the collapsed supernova core (Lai & Goldreich 2000). While the evidence for such kicks is unequivocal (Johnston et al 2005), their physical origin remains unclear.…”
Section: Proper Motionsmentioning
confidence: 99%
“…Lyne & Lorimer (1994) and Hobbs et al (2005) analysed a large number of pulsar proper motions and demonstrated that their transverse velocities are typically several hundred km s −1 . Various explanations have been proposed for these high velocities, including a postnatal electromagnetic rocket mechanism (Harrison & Tademaru 1975), asymmetric neutrino emission in the presence of super-strong magnetic fields (Lai & Qian 1998), hydrodynamical instabilities in the collapsed supernova core (Lai & Goldreich 2000) and the asymmetric explosion of γ-ray bursts (Cui et al 2007). Knowledge of pulsar proper motions and velocities is essential for many aspects of pulsar and neutron star astrophysics including determinations of the birth rate of pulsars, associations with supernova remnants and the Galactic distribution of the progenitor population.…”
Section: Introductionmentioning
confidence: 99%
“…However, what if the expanding of a fireball outside quark surface is not spherically symmetric? An asymmetric explosion may result both in a GRB-like fire jet and in a kick on quark stars, and the statistical result of Cui et al [61] indicated that the kick velocity of pulsars could be consistent with an asymmetric explosion of GRBs.…”
Section: An Idea Of Understanding Grb X-ray Flaresmentioning
confidence: 99%